2014
DOI: 10.1073/pnas.1402905111
|View full text |Cite
|
Sign up to set email alerts
|

New high-resolution computed tomography data of the Taung partial cranium and endocast and their bearing on metopism and hominin brain evolution

Abstract: Falk and colleagues [Falk D, Zollikofer CP, Morimoto N, Ponce de León MS (2012) Proc Natl Acad Sci U S A 109(22):8467-8470] hypothesized that selective pressures favored late persistence of a metopic suture and open anterior fontanelle early in hominin evolution, and they put an emphasis on the Taung Child (Australopithecus africanus) as evidence for the antiquity of these adaptive features. They suggested three mutually nonexclusive pressures: an "obstetric dilemma," high early postnatal brain growth rates, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It was argued in the past that metopism is accompanied by agenesis of the frontal sinuses, although several subsequent studies failed to confirm this (reviewed by Marciniac and Nizankowski, 1959). The oldest known case of metopism, although diagnostically disputed (Holloway et al, ), concerns the 2.5 million year old skull of an Australopithecus africanus child aged 3–4 years and found near Taung, South‐Africa (Hrdlicka, ). This ignited the idea that persistence of the metopic suture well beyond birth, as in modern humans and apparently in earlier hominids but not in chimpanzees or gorillas (our closest living relatives), reflects prolonged growth of the frontal lobes and hence advanced cognitive development (Falk et al, ).…”
Section: Cranial Sutures In Dysplasias and Dysostosesmentioning
confidence: 99%
“…It was argued in the past that metopism is accompanied by agenesis of the frontal sinuses, although several subsequent studies failed to confirm this (reviewed by Marciniac and Nizankowski, 1959). The oldest known case of metopism, although diagnostically disputed (Holloway et al, ), concerns the 2.5 million year old skull of an Australopithecus africanus child aged 3–4 years and found near Taung, South‐Africa (Hrdlicka, ). This ignited the idea that persistence of the metopic suture well beyond birth, as in modern humans and apparently in earlier hominids but not in chimpanzees or gorillas (our closest living relatives), reflects prolonged growth of the frontal lobes and hence advanced cognitive development (Falk et al, ).…”
Section: Cranial Sutures In Dysplasias and Dysostosesmentioning
confidence: 99%
“…In a recent tomography study of the Taung Australopithecus africanus fossil, Carlson and colleagues failed to find any signs of human-infant skull features (Holloway et al, 2014). Previous studies suggested that features of the Taung specimen would allow the child's brain to grow rapidly, similar to brain growth in modern home sapiens.…”
Section: Answering the Lunate Sulcusmentioning
confidence: 99%
“…The type specimen of Australopithecus africanus, Taung, is a juvenile skull consisting of a partial face with fragmentary pieces of the basicranium attached, a mandible, and a natural hemi-endocast. 1 Taung has been the subject of intensive research focus because of its potential to resolve questions about hominin brain size and reorganisation [2][3][4][5][6][7] and A. africanus craniofacial growth [8][9][10][11] , dental maturation [12][13][14][15][16][17][18] and brain ontogeny [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%